Organic Function Layer Interface Behaviour on Phosphorescent Material Device Performance - Gao, Zhixiang; Hao, Yuying; Wang, Hua; Miao, Yanqin; Xu, Bingshe (Asian Journal of Chemistry, 2013)
The interface charges influences on device performances which is captured in organic electroluminescent device (OLED) have become the hotspot of research in organic electroluminescent device, current conduction as well as the carrier and the electric field distribution is very crucial to the understanding of organic light emitting devices, (OLED) microscopic physical processes. This paper prepared a concave and convex interface structure of ITO/NPB/CBP + Ir(ppy)3/liF/Al organic electrophosphorescent devices, with 4,4'-N,N'-two carbazole biphenyl (CBP) as the host material, Ir[ppy)3(tris(2-phenyl pyridine)iridium] as phosphorescent dopant, NPB as a hole transport layer. The different concave and convex emitting layer phosphorescent device of NPB/CBP + Ir(ppy)3 interface is studied and use the current density-voltage-brightness curve and current efficiency-voltage curve analysis device interface charge trapping and injected charge dynamics, determine the optimal convex number of light emitting layer, when the convex number is 3, the maximum current efficiency of this device is 23 cd/A and was 30 % higher than traditional structure device.